Generation of magnetic and chromomagnetic fields at high temperature in the standard model - Demchik, V.I.; Skalozub, V.V. (Вопросы атомной науки и техники, 2001)
The spontaneous generation of the magnetic and chromomagnetic fields at high temperature is investigated in the Standard Model. The consistent effective potential including the one-loop and the daisy diagrams of all boson and fermion fields is calculated. The mixing of the generated fields due to the quark loop diagram is studied.